Six Thinking Hats Method for Developing Critical Thinking Skills - Eunice Widyanti Setyaningtyas; Elvira Hoesein Radia (Journal of Educational Science and Technology (EST), 2019)
The purpose of this research is to assist the student teachers in their final year to think critically in analyzing the lesson plan document in the Kurikulum 2013 framework using the Six Thinking Hats method as a tool. This tool has visual imagery similar to colorful hats, with a specific point of view. The white hat acts as an information source, black hat identifies threats, the red hat represents emotion and intuition, the yellow hat identifies support and strength, the green hat stimulates creative ideas, and the blue hat becomes the leader of the discussion. This is a one-group post-test only experiment. The data is analyzed descriptively and interpreted qualitatively. The instrument is rubrics for analysis, also documentation and interview. The result shows that the average of the analysis scored 27,5 (out of 57) in a "moderate" level. This means students give short analysis with less-detailed description and the reasoning is less clear. The order from the lowest to the highest score is: yellow (scored 1,1)- white (1,2)-green (1,3)-red (1,5)-black (2,0). Although the result is still in the middle level, it still can be seen that this method is very potential to assist students to think critically, with a step by step development.